Дослідження ефективності роботи обладнання для інтенсифікації відтискання технічних олій в гвинтових прес-екструдерах для виготовлення паливних брикетів - Самохвал, Віталій Анатолійович; Самойчук, Кирило Олегович; Samokhval, Vitalii; Samoichuk, Kyryl (Запоріжжя : 2023, 2023)
UA: Актуальність дослідження зумовлена проблемою надмірного вмісту технічних олій в паливних брикетах які виготовлялись з оліємістких сировин, що впливає в значній мірі як на якість брикету так і на екологічні показники. Ця проблема характерна для різних видів конструкцій шнекових пресів для виготовлення паливних брикетів. У зв'язку з цим дане дослідження направлено на знаходження найбільш оптимальних методів виготовлення паливних брикетів на пресах даного типу та розробці і вдосконаленню їх конструкції з метою підняття якості готової продукції. Одними із головних видів для знаходження оптимального вирішення даної проблеми є, емпіричні методи дослідження, за допомогою яких проаналізовано методи та способи удосконалення та здійснена розробка більш інноваційного обладнання для виготовлення паливних брикетів з оліємісткої рослинної сировини. В роботі по вирішенню даної проблеми, проаналізовано особливості відомих конструкцій обладнання шнекового типу для виготовлення паливних брикетів з олієвмісної сировини, та обґрунтовано необхідність розроблення нових формуючих та дожимних робочих органів. EN: The article is formulated relevance of the study is due to the problem of excessive content of industrial oils in fuel briquettes made from oil-containing raw materials, which significantly affects both the quality of the briquette and environmental performance. This problem is typical for different types of screw press designs for the production of fuel briquettes. In this regard, this study aims to find the most optimal methods for manufacturing fuel briquettes on presses of this type and to develop and improve their design in order to improve the quality of finished products. One of the main types for finding the optimal solution to this problem is empirical research methods, which analyze the methods and ways to improve and develop more innovative equipment for the manufacture of fuel briquettes from oil-containing plant material. In order to solve this problem, the features of the known designs of screw-type equipment for the manufacture of fuel briquettes from oil-containing raw materials were analyzed, and the need to develop new forming and pressing working bodies was substantiated. Experiments with the developed new working bodies were carried out. These bodies make it possible to create a controlled process of compression and separation of oils from oil-containing raw materials at each stage of briquette formation. Depending on the number of pressing nozzles, the cycles of compression and oil separation can be repeated many times. The use of the developed nozzles significantly increased the degree of pressure build-up over the entire area from the grinding of the curd to the final formation of the briquette. Due to this, the quality of finished products has improved and the range of raw materials has expanded, as well as the yield of technical oils used for the manufacture of paints, the price of which is several times higher than the briquettes themselves, which means that the companies that will improve their extruders with these working bodies will also increase their profits rameters, molding nozzles, oil yield.
Study of the efficiency of equipment for intensification of squeezing of industrial oils in screw press extruders for the manufacture of fuel briquettes
Самохвал В. А., Самойчук К. О. Дослідження ефективності роботи обладнання для інтенсифікації відтискання технічних олій в гвинтових прес-екструдерах для виготовлення паливних брикетів. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. Запоріжжя : ТДАТУ. 2023. Вип. 13, том 1. C. 198-210.
Keywords: виробництво брикетів; прес; геометричні параметри; формуючі насадки; вихід олії; briquette production; press; geometric parameters; molding nozzles; oil yield